Genome assembly and annotation for red clover (Trifolium pratense; Fabaceae) - Istvánek, Jan; Jaros, Michal; Krenek, Ales; Řepková, Jana (American journal of botany, 2014)
PREMISE OF THE STUDY: Red clover (Trifolium pratense) is an important forage plant from the legume family with great importance in agronomy and livestock nourishment. Nevertheless, assembling its medium-sized genome presents a challenge, given current hardware and software possibilities. Next-generation sequencing technologies enable us to generate large amounts of sequence data at low cost. In this study, the genome assembly and red clover genome features are presented. METHODS: First, assembly software was assessed using data sets from a closely related species to find the best possible combination of assembler plus error correction program to assemble the red clover genome. The newly sequenced genome was characterized by repetitive content, number of protein-coding and nonprotein-coding genes, and gene families and functions. Genome features were also compared with those of other sequenced plant species. KEY RESULTS: Abyss with Echo correction was used for de novo assembly of the red clover genome. The presented assembly comprises ∼314.6 Mbp. In contrast to leguminous species with comparable genome sizes, the genome of T. pratense contains a larger repetitive portion and more abundant retrotransposons and DNA transposons. Overall, 47 398 protein-coding genes were annotated from 64 761 predicted genes. Comparative analysis revealed several gene families that are characteristic for T. pratense. Resistance genes, leghemoglobins, and nodule-specific cystein-rich peptides were identified and compared with other sequenced species. CONCLUSIONS: The presented red clover genomic data constitute a resource for improvement through molecular breeding and for comparison to other sequenced plant species.
Keywords: sekvence nukleotidů; Genes, Plant; Chromosome Mapping; Genome, Plant; genom rostlinný; genome annotation; Trifolium pratense; Sequence Analysis, DNA; sekvenční analýza DNA; rostlinné proteiny; Fabaceae; DNA rostlinná; DNA, Plant; red clover; mapování chromozomů; de novo assembly; Base Sequence; assessment of assembly software; rostlinné geny; Trifolium; Plant Proteins